Etyczne problemy działania agentów zawodników w piłce nożnej - Pawlak, Zbigniew; Smoleń, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2012)
The players’ agent is a middleman who, on the strength of an agent contract and with pay, becomes obliged to act as a go-between in concluding contracts between players and clubs or transfer contracts between clubs. According to data of the International Federation of Association Football (FIFA), at the end of March 2011 there were 5794 licensed agents of football players in 219 national federations. According to the FIFA’s regulations, players, as well as clubs, have right to engage licensed agents in connection with negotiationg or renegotiationg of a player’s employment contract or a player’s transfer. Players and clubs are forbidden using services of unlicensed agents. The FIFA’s Regulations on Players’ Agents – and analogous regulations of the Polish Union of Football – burden the agent with many obligations. Moreover, definite obligations are imposed on clubs and players. Additional regulations introduce a code of players’ agents professional conduct. The player’s agent – as well as the player, the club and the union – can be imposed with sanctions for breaking the abovementioned rules. In milieus connected with Polish football there is a quite common opinion that, in spite of severe sanctions provided by regulations, obligations and rules of professional conduct are often broken in activities of players’ agents. However it is an opinion based on rumours and suppositions, which is not confirmed by decisions of the Department of Discipline of the Polish Union of Football concerning infliction of punishment.